Union of the Comoros : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2010)
Despite offering a more realistic macroeconomic outlook than the I-Poverty Reduction Strategy Paper (PRSP), the baseline scenario under the full Poverty Reduction and Growth Strategy Paper (PRGSP) is overly optimistic. The authorities estimate the cost of the five-year strategy at USD 1.4 billion, nearly all to be funded with assistance from donors. The PRGSP rightly notes the adverse impact of real exchange rate appreciation on external viability. The PRGSP identifies three main sectors-agriculture, fisheries, and tourism-that have the potential to generate sustained economic growth. Comoros's development goals and reform agenda under the full PRGSP are ambitious.